Er3+-doped germanate glasses for active waveguides prepared by Ag+/K+ <-> Na+ ion-exchange - Barbosa, A. J. [UNESP]; Maia, L. J. Q. [UNESP]; Nascimento, A. M. [UNESP]; Goncalves, R. R.; Poirier, G.; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2008)
Planar waveguides were prepared by Ag+/K+ <-> Na+ ion-exchange on Er+3 -doped GeO2-ZnO-Na2O-Li2O glasses obtained by a melting-casting method. Optical parameters of the waveguides were measured at 543.5, 632.8, and 1550 nm by m-line technique as a function of the Ag+ ion-exchange time. The optimized planar waveguides show an effective diffusion depth (d) of 2.95 mu m and well confined propagating TE0 and TM0 modes at 1550 nm. Spectroscopic properties as photoluminescence emission and emission decay time were evaluated for the erbium-doped planar waveguide, indicating that Ag+ <-> Na+ ion-exchange enhance the photoluminescence emissions in the green and infrared regions from erbium ions. The glass system studied is promising to be applied as optical amplifiers in the C-telecom band. Green emission sensitized by Ag+ was also observed. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Ion-exchange; Planar waveguides; Glass transition; Optical spectroscopy; Absorption; Luminescence; FTIR measurements; Germanates; Rare-earths in glasses; Glass transition